Treatment of pelvic stenosis with heterologous graft and subtotal colectomy in a cat - Scorsato, Paulo Sérgio; Rahal, Sheila Canevese [UNESP]; Teixeira, Thainan Lima; Scorsato, Mateus Feital (Universidade Federal do Rio Grande do Sul, 2019)
Background: The management of malunion of pelvic fracture and its complications may require from conservative to surgical methods, depending on the severity and temporal evolution. Thus, the aim of this present report is to describe the treatments adopted in a cat with severe pelvic stenosis. Case: An approximately 3-year-old neutered male crossbreed cat, weighing 3 kg, was presented due to difficulty in defecation in the previous eight months. According to its tutor, the cat was adopted one year earlier, with a history of pelvic fracture due to a run over, which had been treated conservatively. The tutor also mentioned that since the appearance of dyschezia, the cat had only been treated with enemas, but without success. In abdominal palpation, there was presence of pain and a mass of firm content in descending colon topography. The radiographic examination of the pelvis presented an exuberant bone callus, characterizing an old fracture, a consolidation with change of bone axis in the right ischium, together with megacolon and fecaloma. It was initially decided that a liquid glycerin-based enema would be performed, in conjunction with clinical treatment with administration of cisapride, dimethicone and lactulose. Although the medical treatment initially helped improve the clinical picture, the cat presented fecaloma two months later. Surgical treatment was then performed, in which distraction of the pubic symphysis with use of a heterologous cortical bone graft (canine tibia stored in glycerin 98%) was performed, as the tutor was not favorable to colectomy as the first option. However, after one month of intervention, despite good evolution, the animal again showed signs of dyschezia. At this point the tutor agreed to colectomy, which was subtotal with preservation of the ileocolic valve. Discussion: The initial treatment of the cat in this report, with administration of prokinetic, antifoaming agent and laxative was insufficient, as the cat again developed fecaloma after two months of use of such medications. In general, cats presenting dyschezia, with constipation and megacolon over a period of more than 6 months, may present irreversible lesion due to damage to the smooth muscle of the colon, with presence of hypertrophy and neuromuscular degeneration of the organ. The problem had already been explained to the tutor, who preferred the medical treatment, as until then the cat had only been treated with enemas. Several techniques have been used to promote the widening of the pelvic canal, including the pelvic symphysiotomy and use of spacers. Although the autograft stimulates osteogenesis more rapidly, there is difficulty in obtaining bones of adequate size and strength, one of the reasons why the heterologous bone was used in the present case. Even with adequate widening of the pelvic canal, the lesion's evolution over time may have predisposed to irreversible damage of the colon in this case. Among existing techniques for resolution of megacolon in cats, coloplasty, partial colectomy, and subtotal colectomy can be cited. The latter technique was undertaken in the present case, in conjunction with ileocolic junction preservation, which has the advantage of a lower incidence of diarrhea. Thus, thesigns of dyschezia had ceased. In conclusion, the combination of procedures adopted for distraction of the pelvic symphysis and subsequent subtotal colectomy allowed adequate recovery of the animal without relapses during a follow-up period of five years. The use of the heterologous graft (canine tibia) for distraction of the pelvic symphysis behaved as a spacer of adequate size and resistance.
Tratamento de estenose pélvica em gato com enxerto heterólogo e colectomia subtotal
Keywords: Colon; Fracture; Malunion; Surgery